قراءة في عتبات الرواية الجزائرية المعاصرة، "أهداب الخشية، عزفا على أشواق افتراضية، لمنى بشلم أ.زينب تومي - زينب, تومي; عبد الرحمن, بن يطو (جامعة الوادي - University of Eloued, 2021)
يسعى هذا المقال، إلى قراءة متأنية، للعتبات النّصية، التي اهتمّ بها النّقد الأدبي، لما لها، من دور بارز، في الوقوف على خصوصية النّصّ، وتحديد مساراته، وتوجيه المتلقي، إلى فهمه، قراءةً، وتأويلاً، من خلال قراءة ،لعتبات رواية جزائرية. سنحاور، عالم هذه الرواية، رواية (أهداب الخشية، عزفا على أشواق افتراضية) من خلال عتباتها، التي تقوم على محاور أربعة:( الغلاف، الإهداء، المؤلف، فالعنوان)، لنقف، في الأخير، على ما أسفرت عليه قراءتنا لها. This article seeks a careful reading of the textual thresholds, which literary criticism cared about, because of its role in indicating the text, defining its paths, and directing the recipient towards his understanding of reading and interpretation, through reading, the thresholds of an Algerian novel. We'll talk about the novel’s world, the novel “fear's lashes, Strumming on virtual nostalgia” by Mouna Bechlem Through its thresholds, which are based on four axes: (the Cover, the Gifting, the Author, and the Title), let us stand, at the end, on the results of our reading of it.
Keywords: عتبات-العنوان-الغلاف-الإهداء- المؤلف; Thresholds - Title - Cover - Dedication - Author.